An Evaluation of the Compressed-Course Format for Instruction in Accounting . - Howell, William C.; Johnson, L. Todd (The Accounting Review, 1982)
ABSTRACT: Although "compressed-course" offerings are widely found in summer programs and intersessions, little published work has evaluated the efficacy of this format relative to conventional term courses, apparently because the controls necessary for strict comparative research are difficult to implement. This study involved such a comparison between several sections of two accounting courses offered under the most compressed format possible and under a regular semester. All aspects of the courses were virtually identical. Evaluation was in terms of (a) terminal performance, (b) post-course student reactions, and (c) comparison of reactions with prior expectations. Analysis of the data showed the compressed format to be highly comparable to the regular format on both performance and student evaluation profiles. The only differences, both marginal, were in the tendency for perceived stress and instructor effectiveness to be greater under the compressed format. Given the rigor of the experimental controls and the power of the statistical tests used, these findings constitute strong evidence of the efficacy of compressed courses.